ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH INDUK DENGAN PEMERINTAH DAERAH PEMEKARAN (STUDI PADA PEMERINTAH DAERAH ACEH TENGAH DAN PEMERINTAH DAERAH BENER MERIAH TAHUN 2015-2019) - Umar Said Meldego; Suparno Suparno (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
The purpose of this study is to analyze financial performance using the independently ratio, effectiveness ratio, efficiency ratio, and dependency ratio between the regional governments of Central Aceh and Bener Meriah in 2015-2019. This type of research is descriptive quantitative using the ratio analysis method. This study uses LKPD data obtained from the BPK Aceh office. The results showed that the ratio of the independence of the Central Aceh and Bener Meriah regencys was at a very low level. The effectiveness ratio of the regional government of Aceh Tengah has the criteria of Moderately Effective, while the regional government of Bener Meriah has the criteria of Less Effective. The efficiency ratios of the Aceh Tengah and Bener Meriah regencys fall into the Efficient criteria. The dependency ratio of Aceh Tengah and Bener Meriah regencys is classified into very high criteria. The results of different tests indicate that there are differences in financial performance at the level of independence of the Central Aceh region and are truly festive